Front Cover: Mechanochemical Solvent‐Free Conditions for the Synthesis of Pillar[5]arene‐Containing [2]Rotaxanes (Eur. J. Org. Chem. 21/2019). Issue 21 (4th April 2019) - Holler, Michel; Stoerkler, Timothée; Louis, Alexandra; Fischer, Fanny; Nierengarten, Jean‐François
Abstract : The Front Cover shows an artistic view of an inclusion complex resulting from the association of dodecanedioyl dichloride and a pillar[5]arene derivative. The latter has been used to prepare a series of pillar[5]arene‐containing [2]rotaxanes under solvent‐free conditions by solid‐to‐solid ball‐milling with various amine reagents. Importantly, [2]rotaxanes difficult or even impossible to prepare in solution are now easily accessible. More information can be found in the Full Paper by J.‐F. Nierengarten et al.